Screening of differentially expressed proteins in placentas from patients with late‐onset preeclampsia. Issue 2 (10th November 2021) - He, Andong; Wang, Jingyun; Yang, Xiaofeng; Liu, Jia; Yang, Xuesong; Wang, Guang; Li, Ruiman
Abstract: Purpose: Preeclampsia (PE) is a severe disease that endangers the safety of mothers and fetuses worldwide. In the absence of specific treatments, more studies on novel predictive and diagnostic biomarkers for PE are required. Experimental design: Data‐independent acquisition proteomics, with five biological replicates, was used to investigate the protein expression profiles of placental tissues from patients with PE and normal pregnant women. Results: In total, 52 differentially expressed proteins (DEPs) were identified, 34 of them were upregulated and 18 downregulated. Bioinformatics analyses revealed that PE was associated with multiple GO terms and KEGG pathways. Arginase‐1 (ARG1), ferritin light chain (FTL), and RNA cytidine acetyltransferase (NAT10) were identified as hub proteins, which were further validated in placental tissues and maternal plasma by western blot and ELISA. Conclusions and clinical relevance: FTL expression was significantly lower in the placental tissues and early and late pregnancy plasma of patients with PE compared to that in normal pregnant women. This study is the first to propose that FTL may be a potential predictive and diagnostic biomarker for PE; it provides a proteomics insight for understanding the pathological mechanism of this disease.